2019
DOI: 10.1038/s41467-019-11723-7
|View full text |Cite
|
Sign up to set email alerts
|

On demand delivery and analysis of single molecules on a programmable nanopore-optofluidic device

Abstract: Nanopore-based single nanoparticle detection has recently emerged as a vibrant research field with numerous high-impact applications. Here, we introduce a programmable optofluidic chip for nanopore-based particle analysis: feedback-controlled selective delivery of a desired number of biomolecules and integration of optical detection techniques on nanopore-selected particles. We demonstrate the feedback-controlled introduction of individual biomolecules, including 70S ribosomes, DNAs and proteins into a fluidic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 31 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…3) In Stage 2 bunching of multiple AMP/ATP or free AA molecules can occur during translocation, leading to a missed read. In [18] a missed read is simply rejected. Here rejection is not an option, the solution lies in performing multiple measurements after reversing the voltage each time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3) In Stage 2 bunching of multiple AMP/ATP or free AA molecules can occur during translocation, leading to a missed read. In [18] a missed read is simply rejected. Here rejection is not an option, the solution lies in performing multiple measurements after reversing the voltage each time.…”
Section: Discussionmentioning
confidence: 99%
“…This was modified in [15] for the analysis of long DNA strands. Other related structures are described in [16][17][18].…”
Section: Stage 1: Charging Of Trna With An Amino Acid (Aa)mentioning
confidence: 99%
“…A part of the fluorescence light is collected via the orthogonal LC SC waveguides (green arrow) and sent to a photodetector (after filtering), which produces a detection spike as shown in the inset of Figure 5c. The device has sufficient enough sensitivity to detect nucleic acids [275] and viruses [276,277] and has been employed for a pool of applications such as particle trapping and manipulation [278][279][280], optical filtering [281,282], particle sorting [283], atomic spectroscopy [284,285], surface-enhanced Raman spectroscopy (SERS) detection [286], etc. The group has also demonstrated simultaneous multiplexed detection of single viruses using their ARROW optofluidic devices by taking advantage of the interference within a multimode interferometer waveguide [276].…”
Section: On-chip Optical Detection Of Single Moleculesmentioning
confidence: 99%
“…Accordingly, nanopores have been used for exploring RNA translocation dynamics [10], tRNA translocation kinetics [11] and to investigate the folding of RNA pseudoknot structures [12]. Nanopores have also been previously used to detect bacterial 50S ribosomal subunits and control their translocation [13], and recently Rahman et al, reported the programmable delivery of 70S ribosomes with a nanopore integrated in an optofluidic chip [14].…”
Section: Introductionmentioning
confidence: 99%